2022
DOI: 10.1111/phn.13108
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing alertness to premonitory symptoms in stroke patients with pre‐hospital delay

Abstract: Objective The purpose was to explore the alertness of premonitory symptoms in stroke patients with prehospital delay, and to analyze the influencing factors. Design and Sample A cross‐sectional study using the convenience sampling method was conducted in the neurology department of a general hospital between November 2018 and July 2019. A total of 352 stroke patients were participated in the survey. Measures A hierarchical multiple regression was performed to analyze the factors related to the alertness of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Previous studies have focused on the positive effects of social support on timely medical treatment [ 16 , 46 – 48 ]. One Chinese study demonstrated that social support was the only feature in the prediction model that affected decision-making delays in rural stroke patients [ 16 ], which is consistent with our studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the positive effects of social support on timely medical treatment [ 16 , 46 – 48 ]. One Chinese study demonstrated that social support was the only feature in the prediction model that affected decision-making delays in rural stroke patients [ 16 ], which is consistent with our studies.…”
Section: Discussionmentioning
confidence: 99%
“…Without this vital information and a limited treatment window, stroke patients may fail to receive effective treatment. 10 Our project aimed to demonstrate a reduction in hospital decision-making time through use of an orange "stroke alert sticker" placed on patients in the field containing key data including time of onset and home medications. As a critical member of the stroke care team, the nurse was able to play a vital role in coordinating the care among several healthcare providers by being in charge of collecting and disseminating the information on the "stroke alert sticker" to the team at large.…”
Section: Discussionmentioning
confidence: 99%
“…Without this vital information and a limited treatment window, stroke patients may fail to receive effective treatment. 10…”
Section: Discussionmentioning
confidence: 99%
“…23 It generally refers to the SS received from family, friends, and others (relatives or colleagues). 8,24,25 A study in a developing country showed that stroke survivors in Saudi perceived their SS in general as moderate, with higher perceived support being received from family and relatives than from friends. This is because stroke survivors' families value close family relationships, even during the disease; additionally, older Saudi patients prefer to receive care and SS from family members than from other sources of support.…”
Section: Introductionmentioning
confidence: 99%
“…SS can be defined as any support provided outside the formal environment, excluding the support provided by social services or health professionals 23 . It generally refers to the SS received from family, friends, and others (relatives or colleagues) 8,24,25 . A study in a developing country showed that stroke survivors in Saudi perceived their SS in general as moderate, with higher perceived support being received from family and relatives than from friends.…”
Section: Introductionmentioning
confidence: 99%